1996
DOI: 10.1007/bf02532391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes on levels and uptake of putative amino acid neurotransmitters in rat retina and retinal pigment epithelium

Abstract: Free amino acid levels and high affinity uptake of glutamate, aspartate, gamma-aminobutyrate, glycine and taurine were studied in retina and retinal pigment epithelium of streptozotocin diabetic rats. Results show that experimental diabetes produces a generalized fall in the content of free amino acids in both retina and retinal pigment epithelium. With regard to the high affinity uptake, in the two tissues of diabetic animals showed decreased aspartate uptake, enhanced taurine and gamma-aminobutyrate uptake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 25 publications
2
36
1
1
Order By: Relevance
“…Li et al (37) reported an increased accumulation of extracellular glutamate in the neocortex submitted to hyperglycemic ischemia, which was correlated with the cell damage observed. In this study, we reported that diabetes had no effect on both synaptosomal GABA and glutamate transport, which is partially in accordance with the observations of Vilchis and Salceda (8). These authors demonstrated an increment in GABA uptake, without changes in glutamate uptake in diabetic rat retina and retinal pigment epithelium.…”
Section: Diabetes Vol 53 August 2004supporting
confidence: 92%
See 2 more Smart Citations
“…Li et al (37) reported an increased accumulation of extracellular glutamate in the neocortex submitted to hyperglycemic ischemia, which was correlated with the cell damage observed. In this study, we reported that diabetes had no effect on both synaptosomal GABA and glutamate transport, which is partially in accordance with the observations of Vilchis and Salceda (8). These authors demonstrated an increment in GABA uptake, without changes in glutamate uptake in diabetic rat retina and retinal pigment epithelium.…”
Section: Diabetes Vol 53 August 2004supporting
confidence: 92%
“…Several authors have shown that diabetes modifies the levels of free amino acids (7,8) and the accumulation of amino acid neurotransmitters. Vilchis and Salceda (8) reported an increase in taurine and ␥-aminobutyric acid (GABA) uptake, whereas glycine and glutamate uptake remained unaffected in diabetic rat retina and retinal pigment epithelium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we could not detect any substantial increase in retinal taurine concentration in diabetic rats which were fed a taurine-supplemented diet. The retina has a remarkable capacity to maintain taurine concentration [77,78], and any access of retinal taurine is probably rapidly removed after the cessation of food intake.…”
Section: Discussionmentioning
confidence: 99%
“…One important diabetic complication, platelet hyperaggregation, has been normalized by the alteration of bile acids composition through the addition of taurine (Franconi et al 1995). Another complication is T1D retinopathy which have shown significantly less taurine levels in the retina, compared with that in healthy rats (Vilchis & Salceda 1996). Diabetic nephropathy are other major complication of T1D.…”
Section: Diabetes-associated Disturbances In Bile Acids and Gut Micromentioning
confidence: 99%